TRADE IN A VIRTUAL STORE - Shomansurov , Zafarjon (Uzbekistan Open Conference, 2025)
This article examines the theoretical and practical foundations of creating a virtual store and organizing e-commerce. It describes the key advantages of online stores over traditional retail, including reduced costs, process automation, and expanded opportunities for customer engagement. Particular attention is paid to issues of integration with payment systems, methods of user identification and tracking, personal data security, and ensuring customer convenience at all stages of the ordering process.
Keywords: e-commerce; virtual store; Internet trade; payment systems; user identification; online order; mobile commerce; web technologies; chats; microbrowser; plastic cards; bank details